Forest Crime Law Enforcement and the Authority of Forest Police in North Minahasa, North Sulawesi - Gladi Angel Ria Dendape; Linda Lidia Imon (Journal Social Civilecial, 2026)
Forest destruction remains a critical legal and environmental challenge in Indonesia, particularly where illegal logging, forest burning, unauthorized mining, and unlawful plantation activities threaten sustainable forest governance. This study examines the authority of Forest Police in enforcing criminal law against forest destruction in North Minahasa, North Sulawesi. The research applies a normative legal method supported by limited empirical information from relevant forestry institutions. Legal materials were examined through statutory, conceptual, and qualitative juridical analysis, focusing on forestry legislation, environmental law, criminal procedure, and regulations concerning Forest Police and Civil Servant Investigators. The findings show that Indonesian forestry law categorizes forest destruction into multiple criminal offences, including damaging forest-protection facilities, illegal timber harvesting, transporting forest products without valid documents, unlawful mining, forest burning, document falsification, corporate timber laundering, obstruction of enforcement, and abuse of authority by officials. Law No. 18 of 2013 substantially expands criminal liability by addressing organized forest crime, corporate involvement, illicit financing, and misuse of forest permits. Forest Police hold pre-emptive, preventive, and repressive authority, including patrol, document inspection, evidence collection, arrest in flagrante delicto, and investigation when appointed as Civil Servant Investigators. Effective enforcement depends on coordinated investigation with the National Police, procedural compliance, and strengthened institutional capacity.